Quick-setting waste-based foaming material as well as preparation method and application thereof
By using the ternary synergistic effect of high-calcium minerals, aluminate cement and carboxylate-containing retarder in cement-based foaming materials, combined with the use of water reducing agent, foam stabilizer and foaming agent, the shortcomings in the early strength and cell uniformity of cement-based foaming materials are solved, and better 2h early strength and cell uniformity are achieved.
Patent Information
- Application Number
- CN202311180080.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
AI Technical Summary
The existing cement-based foaming materials have shortcomings in early strength and cell uniformity, especially the problems of strength and cell uniformity in early 2 hours have not been effectively solved.
By using the three-part synergistic effect of high-calcium minerals, aluminate cement and carboxylate-containing retarder in cement-based foaming materials, the setting time is regulated, and combined with the use of water reducing agent, foam stabilizer and foaming agent, a fast solidification waste-based foaming material with better early strength and cell uniformity is prepared.
A significant improvement in the early strength of 2h was achieved, while ensuring the uniformity of cell distribution, solving the problem of taking into account early strength and cell uniformity.
Smart Images

Figure BDA0004446927870000121 
Figure BDA0004446927870000131 
Figure BDA0004446927870000132
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foaming materials, and in particular to a rapid-setting waste-based foaming material and a preparation method and application thereof. Background Art
[0002] Chinese patent application CN109111161A discloses a cement-based foaming material and a preparation method thereof, wherein the cement-based foaming material is composed of the following raw materials in parts by weight: 40-55 parts of cement, 15-30 parts of zeolite, 1.0-2.0 parts of polyacrylate emulsion, 0.6-1.5 parts of water reducer, 0.3-0.7 parts of glass fiber, 4-8 parts of foaming agent, and 20-30 parts of water. The foaming agent used is composed of the following components in parts by weight: 2-10 parts of redispersible latex powder, 1-5 parts of methyl cellulose ether, 10-30 parts of metakaolin, and 65-85 parts of calcium-based bentonite.
[0003] Chinese patent application CN 108821671 A discloses a high-strength ready-to-use foamed concrete material made from all industrial solid waste and a preparation method thereof, the preparation method comprising the following steps: (1) uniformly mixing a cementitious material with phosphogypsum, fly ash and carbide slag, grinding the mixture to obtain a mixture, adding the mixture to a stirring tank, stirring with warm water, adding a foaming agent and continuing to stir, and then forming the slurry; (2) demolding the slurry after hardening in step (1), and curing at room temperature and pressure to obtain foamed concrete; the cementitious material comprises the following components: 14%-16% aluminum ash, 24%- 26% red mud, 43%-45% carbide slag, 16%-18% phosphogypsum; the preparation method of the cementitious material comprises the following steps: 1) mixing aluminum ash, red mud, carbide slag and phosphogypsum, grinding with a wet pulverizer to obtain a mixture; 2) adding the mixture in step 1) into a homogenizing tank, washing with water to obtain a homogenized material; 3) filtering the homogenized material in step 2), drying and grinding to obtain a powdered mixture; 4) calcining the powdered mixture in step 3), and rapidly cooling after calcination to obtain a cementitious material.
[0004] However, none of the above-mentioned prior arts has proposed a solution on how to improve the early strength (such as 2h early strength) of cement-based foamed materials and how to ensure good cell uniformity of the foaming system. Summary of the invention
[0005] The present invention provides a rapid-setting waste-based foaming material, a preparation method and an application thereof. Based on the formulation system of the present invention, a rapid-setting waste-based foaming material with better early strength, especially better 2h early strength, can be obtained, and the obtained material can also have good pore uniformity.
[0006] To achieve the purpose, the present invention provides the following technical solutions:
[0007] In one aspect, the present invention provides a rapid-setting waste-based foaming material, which is prepared by using raw materials including the following components, in parts by mass:
[0008] Aluminate cement 10-50 parts, high calcium mineral 10-80 parts, retarder 0.01-2 parts, water reducer 0.001-2 parts, foam stabilizer 0.01-1 parts, thickener 0-5 parts, foaming agent 0.005-15 parts;
[0009] Wherein, the mass content of free calcium oxide in the high-calcium mineral is 2-40wt%, preferably 5-20wt%;
[0010] The mass ratio of the aluminate cement to the high calcium mineral is 2-5:1 or 1:2-8;
[0011] The retarder is an organic acid containing a carboxylate group.
[0012] Based on the formulation system of the present invention, high calcium minerals and aluminate cement with a specific free calcium oxide content are used in a specific ratio, and a retarder, a water reducer and a foam stabilizer are added, and a slurry gel material is obtained by mixing with water, and a solid waste-based foaming material can be obtained by adding a chemical foaming agent or a physical foaming agent to obtain a foam. In addition, under the formulation system of the present invention, there is a ternary synergistic effect between high calcium minerals, aluminate cement and a carboxylate-containing retarder, which can play a role in regulating the setting time, and is conducive to obtaining a foaming material that takes into account good early strength (2h early strength) and uniform pores.
[0013] The inventors have found that by using the formula system of the present invention, high calcium minerals, carboxylate-containing retarders and aluminate cement are used in combination according to specific dosages, and there is a certain synergistic effect between the three. Adding high calcium minerals to aluminate cement, and then by compounding carboxylate-containing retarders, by controlling the ratio of aluminate cement and high calcium minerals, the retarder can play a retarding effect or a quick setting effect, which can effectively regulate the setting time, facilitate construction, and obtain good 2h early strength at the same time. This is completely different from the effect of adding retarders to cement in the past. Conventional operations add retarders to cement to extend the setting time, but the early strength will also be greatly reduced. The present invention is based on the high calcium mineral / carboxylate-containing retarder / aluminate cement ternary system, and a water reducer, a foam stabilizer and a chemical foaming agent are added thereto to prepare a quick-setting waste-based foaming material. In the present invention, by combining the components with each other, and introducing a foam stabilizer and a water reducer, etc., it is possible to play a role in regulating the viscosity (fluidity) of the slurry, which is conducive to uniform distribution of pores without collapse and pore breakage.
[0014] The inventors found that in the formula system of the present invention, the mass ratio of aluminate cement and high calcium mineral is controlled at 2-5:1 or 1:2-8, and adding a retarder on this basis can play a role of quick setting or slow setting, obtain an initial setting time that is beneficial to the construction of the foaming system to prepare a quick-setting solid waste foaming material, and can obtain good 2h early strength. Specifically, the inventors found that when the mass ratio of the aluminate cement and the high calcium mineral is ≥2:1 and less than 3:1 or 1:2-3, if no retarder is added, the initial setting time is too short (for example, less than 20min, or even within 10 minutes), resulting in the foaming system not having time to produce pores, and it is difficult to obtain a foaming material with uniform pore distribution, and adding a retarder on this basis can play a slow setting effect, for example, in the formula system of the present invention, the initial setting time can be made 10-60min, or for example, within 20-60min, which is beneficial to the foaming system to obtain a good foaming effect, and the resulting material has better pore uniformity, and takes into account the acquisition of good early strength. In addition, the inventors have also found that when the mass ratio of the aluminate cement to the high calcium mineral is 3-5:1 or <1:3 and ≥1:8, if no retarder is added, the initial setting time is too long (for example, more than 1 hour or even more than several hours), which is not conducive to construction. On this basis, adding a retarder can play a role in rapid setting. For example, in the formulation system of the present invention, the initial setting time can be within 10-60 minutes, for example, within 20-60 minutes, and better early strength can be obtained.
[0015] In the present invention, the high calcium mineral refers to a mineral with a high free calcium oxide content. High calcium fly ash such as pulverized coal furnace fly ash with a calcium content of more than 5% or even more than 10% cannot achieve the above-mentioned synergistic effect of the present invention with aluminate cement. The calcium oxide in pulverized coal furnace fly ash is mainly inert calcium oxide; while the calcium oxide in circulating fluidized bed fly ash mainly exists as free calcium oxide. The use of circulating fluidized bed fly ash with a free calcium oxide content of 2-40% can achieve the above-mentioned ternary synergistic effect with aluminate cement and carboxylate-containing retarder.
[0016] Preferably, the retarder is tartaric acid.
[0017] In some embodiments, the high calcium mineral is selected from one or more of tourmaline slag, fly ash, limestone, and gypsum.
[0018] In some embodiments, the fly ash is selected from circulating fluidized bed fly ash.
[0019] In some embodiments, the water reducer is selected from one or more of naphthalene-based water reducers, polycarboxylate water reducers, and lignin-based water reducers, preferably polycarboxylate water reducers.
[0020] Preferably, the foam stabilizer is selected from hydroxypropyl methylcellulose with a viscosity of ≥10000 mPa·s. In the formulation system of the present invention, the use of hydroxypropyl methylcellulose with the preferred viscosity as the foam stabilizer is conducive to obtaining a gelling material with better fluidity, forming a foam with a stable structure in the subsequent foaming process, and facilitating uniform distribution of the foam.
[0021] Specifically, the foaming agent is selected from a chemical foaming agent or a physical foaming agent. The amount of the foaming agent can be 0.005-15 parts, and the amount can be determined according to the specific requirements of the foaming material. For example, in some embodiments, the foaming agent is a chemical foaming agent, and the amount is 0.5-15 parts; for example, in some embodiments, the foaming agent is a physical foaming agent, and the amount of the foaming agent is, for example, 0.005-8 parts.
[0022] Preferably, the chemical foaming agent is hydrogen peroxide. More preferably, the chemical foaming agent is hydrogen peroxide with a mass concentration of 30-40%. Using hydrogen peroxide of this preferred concentration as a foaming agent in the formulation system of the present invention is conducive to obtaining a better foaming effect; if the concentration of hydrogen peroxide is too low, the foam cells are flat and uneven in size; if the concentration of hydrogen peroxide is too high, not only the cost increases, but also it is easy to cause too much foaming, affecting the foaming effect.
[0023] Preferably, the physical foaming agent is one or more of an animal protein foaming agent and a composite protein foaming agent. The composite protein foaming agent is, for example, a compound of two or more protein foaming agents, a compound of a protein foaming agent and other components, or a modified protein foaming agent; specifically, for example, it can be a compound of a plant protein and an animal protein foaming agent. The above-mentioned foaming agents can all be commercially available products. Preferably, when the foaming agent is a physical foaming agent, the amount of the thickener is 0.001-5 parts; preferably, the thickener is a renewable latex powder, such as 4036N type, 5010N type latex powder, etc.
[0024] In some embodiments, the rapid-setting waste-based foaming material is prepared by using raw materials including the following components, in parts by mass: 10-50 parts of aluminate cement, 10-80 parts of high-calcium minerals, 0.01-2 parts of retarder, 0.001-2 parts of water reducer, 0.01-1 parts of foam stabilizer, 0-5 parts of thickener, and 0.5-15 parts of chemical foaming agent. In some embodiments, the rapid-setting waste-based foaming material is prepared by using raw materials including the following components, in parts by mass: 10-50 parts of aluminate cement, 10-80 parts of high-calcium minerals, 0.01-2 parts of retarder, 0.001-2 parts of water reducer, 0.01-1 parts of foam stabilizer, 0.001-5 parts of thickener, and 0.005-8 parts of physical foaming agent.
[0025] In some better embodiments, the quick-setting waste-based foaming material is prepared from raw materials including the following components, in parts by mass: 10-45 parts of aluminate cement, 10-60 parts of high-calcium mineral, 0.1-0.5 parts of retarder, 0.001-2 parts of water reducer, 0.01-1 parts of foam stabilizer, 0-5 parts of thickener, and 0.005-15 parts of foaming agent; wherein the mass content of free calcium oxide in the high-calcium mineral is 2-40wt%; the mass ratio of the aluminate cement to the high-calcium mineral is 2-4:1 or 1:2-5; and the retarder is tartaric acid. The use of the preferred formula system is conducive to taking into account both better 2h early strength and good cell uniformity.
[0026] The present invention also provides a method for preparing the above-mentioned rapid solidification waste-based foaming material, comprising the following steps:
[0027] (1) mixing the aluminate cement, high calcium mineral, retarder, water reducer, foam stabilizer and optional thickener with water to obtain a cementitious material;
[0028] (2) When the foaming agent is a chemical foaming agent, the chemical foaming agent is added to the gelling material and stirred, the resulting mixture is injected into a mold, and after curing and molding, the mold is demolded to obtain the rapid-setting waste-based foaming material;
[0029] When the foaming agent is a physical foaming agent, the physical foaming agent is diluted to prepare foam, and then the obtained foam is mixed and stirred with the gelling material, and the obtained mixture is injected into a mold, and after curing and molding, the mold is demolded to obtain the rapid-setting waste-based foaming material; preferably, the dilution is to dilute the physical foaming agent with water by 30-50 times the mass;
[0030] Specifically, the amount of water used in step (1) is, for example, 0.2-1.0 times, for example, 0.2-0.8 times, the total mass of the aluminate cement and the high-calcium mineral.
[0031] Based on the formulation system of the present invention, a quick-setting waste-based foaming material with the following characteristics can be obtained: 10min≤initial setting time≤60min, for example, 20min≤initial setting time≤60min, final setting time≤120min, 2h compressive strength≥0.1MPa, and fluidity of 390-460mm, for example, 390-440mm, for example, 400-460mm. Through the formulation system of the present invention, the initial setting time is more than 10min or more than 20min. For chemical foaming agents, it is beneficial to produce pores by chemical reaction, and it will not produce pores in time due to too short time (for example, less than 20min), which affects the foaming effect; for physical foaming agents, it will not cause serious defoaming during the hardening process due to too short initial setting time, and it will not cause too short time to produce pores, which is beneficial to obtain a better foaming effect; and the initial setting time does not exceed 60min, which is not only beneficial to improve construction efficiency, but also beneficial to obtain early strength.
[0032] The present invention also provides an application, wherein the quick-setting waste-based foaming material or the quick-setting waste-based foaming material obtained by the preparation method is used in thermal insulation wall materials, lightweight filling materials or 3D printing materials.
[0033] The technical solution provided by the present invention has the following beneficial effects:
[0034] The formula system of the present invention can obtain a quick-setting solid waste-based foaming material with better early strength (especially 2h early strength) through the interaction of each component. At the same time, the formula system based on the present invention can obtain a cementitious material with better fluidity through the combination of each component, and by introducing a chemical foaming agent or a physical foaming agent into the cementitious material to obtain a foam, a foaming material with uniform pore distribution can be obtained. In addition, the concrete material provided by the present invention has a large amount of solid waste, which can effectively reduce material costs and solve the problem of solid waste accumulation; at the same time, the material preparation process is simple, and it has practicality and industrial feasibility. DETAILED DESCRIPTION
[0035] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0036] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0037] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.
[0038] The detection methods involved in the embodiments or comparative examples are described as follows:
[0039] Initial setting time: Tested in accordance with GBT 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures";
[0040] Final setting time: Tested in accordance with GBT 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures";
[0041] 2h compressive strength: tested in accordance with GBT 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete";
[0042] Detection method of free calcium oxide in high-calcium minerals: Test in accordance with GB / T 176-2017 "Chemical Analysis Methods for Cement";
[0043] Fluidity: Determined according to the expansion test method specified in GB / T 50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials".
[0044] Unless otherwise specified, the “parts” mentioned in the following examples refer to parts by mass.
[0045] Example 1
[0046] (1) The raw materials used in this embodiment are described as follows:
[0047] High calcium mineral: circulating fluidized bed fly ash with an average particle size of 18.9 microns. Its main components include 20.2wt% SiO2, 10.5wt% Al2O3, 43.3wt% CaO (free calcium oxide and inert calcium oxide), and 8.8wt% Fe2O3; among which the free calcium oxide content is 20wt%.
[0048] Cement: Aluminate cement, Zhengzhou Jianai Special Aluminate Co., Ltd.
[0049] Retarder and water reducer: provided by Nanjing Stabbo Trading Co., Ltd., the retarder is tartaric acid (L+), and the water reducer is polycarboxylate water reducer 530P.
[0050] Foam stabilizer: Hydroxypropyl methylcellulose with a viscosity of 10000 mPa·s, provided by Hebei Haoshuo Chemical Co., Ltd.
[0051] Chemical foaming agent: 30% mass concentration of hydrogen peroxide, analytical grade, provided by Hangzhou Jingxin Chemical.
[0052] (2) Preparation of rapid solidification waste-based foaming materials
[0053] 10 parts of aluminate cement and 40 parts of high calcium mineral were uniformly mixed, and 0.2 parts of retarder, 0.13 parts of water reducer, 0.05 parts of foam stabilizer and 25 parts of water were added. The mixture was first slowly stirred at a speed of 62±5r / min for 20s, and then quickly stirred at a speed of 125±10r / min for 30s to obtain a cementitious material; 5 parts of chemical foaming agent were added to the cementitious material and quickly stirred at a speed of 125±10r / min for 20s, and then injected into the mold, and demolded after curing and molding to obtain a quick-setting waste-based foaming material. The experimental results are shown in Table 2.
[0054] After carrying out Example 1, the following comparative experiment was also carried out: on the basis of Example 1, no foam stabilizer was added, and as a result, the uniformity of the pore distribution of the obtained foaming material was significantly deteriorated.
[0055] Example 2
[0056] The method was carried out in accordance with Example 1, except that the amount of each component in the formula was changed, as shown in Table 1;
[0057] The high calcium mineral used is: circulating fluidized bed fly ash, with an average particle size of 17.6 microns, a total calcium oxide content of 8wt%, and a free calcium oxide content of 5wt%.
[0058] Example 3
[0059] The method is carried out in accordance with Example 1, except that the amount and proportion of aluminate cement and high calcium mineral are changed, as shown in Table 1.
[0060] Example 4
[0061] The method was carried out in accordance with Example 1, except that the amount of each component in the formula was changed, as shown in Table 1;
[0062] The high calcium mineral used is tourmaline slag, with an average particle size of 19.2 microns, a total calcium oxide content of 63wt%, and a free calcium oxide content of 40wt%.
[0063] Example 5
[0064] The method was carried out in accordance with Example 1, except that the amount of each component in the formula was changed, as shown in Table 1;
[0065] The high calcium mineral used is limestone with an average particle size of 21 microns, a total calcium oxide content of 56 wt %, and a free calcium oxide content of 2 wt %.
[0066] Example 6
[0067] The method is carried out in accordance with Example 4, except that the amount and proportion of aluminate cement and high calcium mineral are changed, as shown in Table 1.
[0068] Example 7
[0069] (1) The raw materials used in this embodiment are described as follows:
[0070] High calcium mineral: circulating fluidized bed fly ash with an average particle size of 18.9 microns. Its main components include 20.2wt% SiO2, 10.5wt% Al2O3, 43.3wt% CaO (free calcium oxide and inert calcium oxide), and 8.8wt% Fe2O3; the free calcium oxide content is 20wt%.
[0071] Cement: Aluminate cement, Zhengzhou Jianai Special Aluminate Co., Ltd.
[0072] Retarder and water reducer: provided by Nanjing Stabo Trading Co., Ltd., the retarder is tartaric acid (L+), and the water reducer is polycarboxylate water reducer 530p.
[0073] Foam stabilizer: Hydroxypropyl methylcellulose with a viscosity of 20000 mPa·s, provided by Hebei Haoshuo Chemical Co., Ltd.
[0074] Thickener: Renewable latex powder 4036N, provided by Hebei Haoshuo Chemical Co., Ltd.
[0075] Physical foaming agent: animal protein, Weihai Zhongsheng New Building Materials Co., Ltd.
[0076] (2) Preparation of rapid solidification waste-based foaming materials
[0077] 10 parts of aluminate cement and 40 parts of high calcium mineral were uniformly mixed, and 0.2 parts of retarder, 0.13 parts of water reducer, 0.14 parts of foam stabilizer, 0.23 parts of thickener and 30 parts of water were added. The mixture was first slowly stirred at a speed of 62±5r / min for 20s in a mixer, and then quickly stirred at a speed of 125±10r / min for 30s to obtain a cementitious material; 0.05 parts of physical foaming agent were diluted 40 times by weight with water, and then prepared into foam by a foaming machine, and then the prepared foam and cementitious material were slowly stirred and mixed at a speed of 62±5r / min, and then injection molded. After curing and molding, the fast-setting foaming material was obtained by demolding. The experimental results are shown in Table 2.
[0078] Example 8
[0079] Refer to Example 7, except that:
[0080] Change the amount of each component in the formula, see Table 1 for details;
[0081] The high calcium mineral used is: circulating fluidized bed fly ash, with an average particle size of 18.5 microns, a total calcium oxide content of 6wt%, and a free calcium oxide content of 3wt%.
[0082] Example 9
[0083] Refer to Example 7, except that:
[0084] Change the amount of each component in the formula, see Table 1 for details;
[0085] The high calcium mineral used is: tourmaline slag, with an average particle size of 18.8 microns, a total calcium oxide content of 54%, and a free calcium oxide content of 39wt%.
[0086] Example 10
[0087] Refer to Example 7, except that:
[0088] Change the amount of each component in the formula, see Table 1 for details;
[0089] The high calcium mineral used is circulating fluidized bed fly ash, with an average particle size of 19.3 microns, a total calcium oxide content of 24 wt%, and a free calcium oxide content of 11 wt%.
[0090] Comparative Examples 1-3
[0091] The same method is used as in Example 1, except that the dosage of each component is changed. The dosage of each component in the formula is shown in Table 1, and the experimental results are shown in Table 2.
[0092] Comparative Examples 4-7
[0093] Comparative Example 4 was carried out with reference to Example 1, except that no retarder was added.
[0094] Comparative Example 5 was carried out with reference to Example 5, except that no retarder was added.
[0095] Comparative Example 6 was carried out with reference to Example 6, except that no retarder was added.
[0096] Comparative Example 7 was carried out with reference to Example 3, except that no retarder was added.
[0097] Comparative Example 8
[0098] The method is carried out with reference to Example 1, except that the high calcium mineral used is fly ash from a pulverized coal furnace, in which the total calcium oxide content is 13 wt % and the free calcium oxide content is 1.5 wt %.
[0099] Comparative Example 9
[0100] The method is carried out with reference to Example 1, except that the free calcium oxide content of the high calcium mineral used is 42 wt%.
[0101] Comparative Example 10
[0102] The same method is carried out as in Example 1, except that tartaric acid is replaced by citric acid.
[0103] Comparative Example 11
[0104] The method was carried out in accordance with Example 1, except that aluminate cement was replaced by silicate cement (Zuanpai P·O42.5R, Yanshan Holding Group Co., Ltd.).
[0105] Comparative Example 12
[0106] The method is carried out with reference to Example 1, except that aluminate cement is replaced by sulphoaluminate cement (425 grade sulphoaluminate cement, Henan Nuoji Building Materials Co., Ltd.).
[0107] Table 1 Formula table of Examples 1-6 and Comparative Examples 1-4 (parts by mass)
[0108]
[0109]
[0110] Note: The "liquid-to-solid mass ratio" in Table 1 refers to the mass ratio of water to the total amount of aluminate cement and high calcium minerals.
[0111] Table 2 Experimental results
[0112]
[0113]
[0114] In Table 2, the cell uniformity is determined by cutting the hardened foamed material and observing the uniformity of the cell size in the cross section. The cell uniformity of the material obtained in Example 1 is used as a comparison benchmark, and the cell uniformity of each example and comparative example is determined to be good, relatively good, and poor by the degree of proximity between the cell uniformity of each example and comparative example and that of Example 1. Foam stability is determined by observing whether the phenomenon of slurry collapse caused by cell defoaming occurs during the hardening process of the material. If this phenomenon occurs, the foam stability is determined to be poor, and if this phenomenon does not occur, the foam stability is determined to be good.
[0115] It can be seen from the above experimental results that by adopting the formulation system of the present invention, a quick-setting waste-based foaming material with better comprehensive performance can be obtained. The initial setting time of the obtained material is within 10-60min (for example, the initial setting time is within 20-60min), and the final setting time is ≤120min. The obtained material has a 2h compressive strength of ≥0.1MPa, and can take into account both better foam stability and good pore uniformity.
[0116] Compared with the examples, the mass ratio of aluminate cement to high calcium mineral in comparative examples 1-3 does not satisfy 2-5:1 or 1:2-8, the obtained material does not have 2h early strength, and the foam stability and / or pore uniformity of the obtained foamed material are relatively poor.
[0117] Compared with Example 1, Comparative Example 4 did not add retarder, and compared with Example 5, Comparative Example 5 did not add retarder. As a result, the initial setting time and final setting time of Comparative Examples 4 and 5 were significantly prolonged compared with Examples 4 and 5, respectively, and it was difficult to obtain 2h early strength, and the foam stability of the foaming material was poor.
[0118] Compared with Example 6, Comparative Example 6 does not add retarder. Compared with Example 3, Comparative Example 7 does not add retarder. As a result, the initial setting time of Comparative Examples 6 and 7 is significantly shortened to less than 10 minutes compared with Examples 6 and 3, respectively. Although it has better 2h early strength, the initial setting time is too short, which affects the foaming effect of the foaming system, and the obtained material has poor foam stability and poor pore uniformity.
[0119] Compared with the examples, the free calcium oxide content of the high calcium mineral used in Comparative Example 8 is less than 2%, and the obtained material does not have 2h early strength. Compared with the examples, the free calcium oxide content of the high calcium mineral used in Comparative Example 9 is too high (reaching 42%), and although the obtained material has good early strength, the foam stability is poor and the cell uniformity is poor.
[0120] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A rapid solidifying waste-based foaming material, characterized in that: The quick-setting waste-based foaming material is prepared by using raw materials including the following components, in parts by mass: Aluminate cement 10-50 parts, high calcium mineral 10-80 parts, retarder 0.01-2 parts, water reducer 0.001-2 parts, foam stabilizer 0.01-1 parts, thickener 0-5 parts, foaming agent 0.005-15 parts; Wherein, the mass content of free calcium oxide in the high-calcium mineral is 2-40wt%, preferably 5-20wt%; The mass ratio of the aluminate cement to the high calcium mineral is 2-5:1 or 1:2-8; The retarder is an organic acid containing a carboxylate group.
2. The rapid solidifying waste-based foaming material according to claim 1, characterized in that: The retarder is tartaric acid.
3. The rapid solidifying waste-based foaming material according to claim 1 or 2, characterized in that: The high calcium mineral is selected from one or more of tourmaline slag, fly ash, limestone and gypsum; Preferably, the fly ash is selected from circulating fluidized bed fly ash.
4. The early-strength, fast-setting lightweight concrete material according to any one of claims 1 to 3, characterized in that: The water reducer is selected from one or more of naphthalene-based water reducers, polycarboxylate-based water reducers, and lignin-based water reducers, preferably polycarboxylate-based water reducers.
5. The rapid-setting waste-based foaming material according to any one of claims 1 to 3, characterized in that: The foam stabilizer is selected from hydroxypropyl methylcellulose with a viscosity of ≥10000 mPa·s.
6. The rapid-setting waste-based foaming material according to any one of claims 1 to 4, characterized in that: The foaming agent is selected from a chemical foaming agent or a physical foaming agent; Preferably, the amount of the chemical foaming agent is 0.5-15 parts; Preferably, the amount of the physical foaming agent is 0.005-8 parts; Preferably, the chemical foaming agent is hydrogen peroxide; more preferably, the mass concentration of the hydrogen peroxide is 30-40%; Preferably, the physical foaming agent is one or more of an animal protein foaming agent and a composite protein foaming agent.
7. The rapid solidifying waste-based foaming material according to claim 6, characterized in that: When the foaming agent is a physical foaming agent, the thickener is preferably used in an amount of 0.001-5 parts; Preferably, the thickener is renewable latex powder.
8. The rapid-setting waste-based foaming material according to any one of claims 1 to 7, characterized in that: The quick-setting waste-based foaming material is prepared by using raw materials including the following components, in parts by mass: Aluminate cement 10-45 parts, high calcium mineral 10-60 parts, retarder 0.1-0.5 parts, water reducer 0.001-2 parts, foam stabilizer 0.01-1 parts, thickener 0-5 parts, foaming agent 0.005-15 parts; Wherein, the mass content of free calcium oxide in the high-calcium mineral is 2-40wt%; The mass ratio of the aluminate cement to the high calcium mineral is 2-4:1 or 1:2-5; The retarder is tartaric acid.
9. The method for preparing the rapid solidifying waste-based foaming material according to any one of claims 1 to 8, characterized in that: The steps include: (1) mixing the aluminate cement, high calcium mineral, retarder, water reducer, foam stabilizer and optional thickener with water to obtain a cementitious material; (2) When the foaming agent is a chemical foaming agent, the chemical foaming agent is added to the gelling material and stirred, the resulting mixture is injected into a mold, and after curing and molding, the mold is demolded to obtain the rapid-setting waste-based foaming material; When the foaming agent is a physical foaming agent, the physical foaming agent is diluted to prepare foam, and then the obtained foam is mixed and stirred with the gelling material, and the obtained mixture is injected into a mold, and after curing and molding, the mold is demolded to obtain the rapid-setting waste-based foaming material; preferably, the dilution is to dilute the physical foaming agent with water by 30-50 times the mass; Preferably, the amount of water in step (1) is 0.2-1.0 times, for example, 0.2-0.8 times, the total mass of the aluminate cement and the high-calcium mineral.
10. An application, characterized in that: The rapid-setting waste-based foaming material described in any one of claims 1 to 8 or the rapid-setting waste-based foaming material prepared by the preparation method described in claim 9 is used in thermal insulation wall materials, lightweight filling materials or 3D printing materials.
Citation Information
Patent Citations
Full industrial solid waste high strength ready-to-use foamed concrete material and preparation method thereof
CN108821671A
Cement-based foaming material and preparation method thereof
CN109111161A